Analisis Pengaruh Laju Kalor Kondensor HTC terhadap Kinerja Sistem Refrigerasi Cascade Dengan Refrigerant Hidrokarbon - Hendri Hendri; Suhengki Suhengki; Roswati Nurhasanah; Prayudi Prayudi (JURNAL POWERPLANT, 2019)
The need for low temperature storage rooms has not been fulfilled with a single refrigeration system. The problem with a single system is that vacuum pressure is needed to reach very low temperatures. The cascade refrigeration system with two HTC and LTC circuits was developed to answer the problem of low temperature space with hydrocarbon refrigerant. The research was carried out experimentally in the PLN IT Refrigeration System Laboratory. This research uses MC134-R404A and MC22-R404A refrigerant pairs, and uses a heat exchanger plate heat exchanger. From the analysis it was found that the MC22-R404A refrigerant pair had better performance COP, HRR, ratio mass than the MC134-R404A. From the research also obtained the results that the installed heat exchanger cannot work optimally. The results of this study will be very useful for developing further research in developing low temperature storage